PERAN PIMPINAN KEPERAWATAN DALAM MENINGKATKAN PATIENT SAFETY DI RUMAH SAKIT - Samfriati Sinurat; Santa Lusya (Program Studi Ners UNIVERSITAS SARI MUTIARA INDONESIA, 2018)
Patient Safety is a patient who is free from potential injury either happen or not as illness, injury and death in health care. In terms of improving patient safety required elements of leadership roles in the field of nursing care program encourages patient safety, reduce the incidence of unintended communication in decision making patient safety, adequate resources and the effectiveness of the contribution in improving patient safety. The purpose of research is to identify the role of leader of the field of nursing services in improving patient safety diruang inpatient Elizabeth Hospital Medan in 2016. The study design was descriptive. Mechanical sampling using non-random sampling (non-probability) with the formula Slovin, totaling 143 respondents using questionnaires leadership role in the field of nursing services improve patient safety with 24 questions ordinal scale. The results obtained by univariate analysis the role of elements of leadership to the field of nursing services in improving patient safety in the inpatient unit Elizabeth Hospital Medan in 2016 found that the highest, respondents expressed either as many as 97 people (67.8%), and a low of respondents stating quite as many as 46 people (32.2%). Expected led the field of nursing services can still play an increasing role in improving patient safety in the inpatient unit Elizabeth Hospital Medan to maintain the quality of nursing services.